Emotional Recognition and Empathy both in Deaf and Blind Adults. (21st January 2019) - Martins, Ana Teresa; Faísca, Luís; Vieira, Helena; Gonçalves, Gabriela
Abstract: Studies addressing the recognition of emotions in blind or deaf participants have been carried out only with children and adolescents. Due to these age limits, such studies do not clarify the long-term effects of vision and hearing disabilities on emotion recognition in adults. We assessed the ability to recognize basic emotions in 15 deaf adults (aged 32.4 ± 8.1 yrs) and in 15 blind adults (48.3 ± 10.5 yrs). Auditory and visual stimuli expressing six basic emotional states were presented to participants (Florida Affect Battery ). Participants also performed an empathy test. Deaf participants showed difficulties in emotion recognition tasks compared to the typical hearing participants; however, differences were only statistically reliable for Facial Emotion Discrimination and Naming tasks (specifically, naming expressions of fear). Deaf participants also revealed inferior levels of cognitive empathy. Concerning blind participants, their performance was lower than the controls' only when the task required the evaluation of emotional prosody while ignoring the semantic content of the sentence. Overall, although deaf and blind participants performed reasonably well on tasks requiring recognition of basic emotions, sensory loss may hinder their social perception skills when processing subtle emotions or when the extraction of simultaneous prosodic and semantic information is required.